Evaluation of a Histoplasma antigen lateral flow assay for the rapid diagnosis of progressive disseminated histoplasmosis in Colombian patients with AIDS. Issue 2 (27th November 2019) - Cáceres, Diego H.; Gómez, Beatriz L.; Tobón, Angela M.; Chiller, Tom M.; Lindsley, Mark D.
Summary: Background: Progressive disseminated histoplasmosis (PDH) is an important cause of mortality in persons living with HIV (PLHIV), especially in countries where patients have limited access to antiretroviral therapies and diagnostic testing. Objective: A lateral flow assay (LFA) to detect Histoplasma capsulatum antigen in serum developed by MiraVista ® was evaluated. Methods: We tested 75 serum samples: 24 from PLHIV and culture‐proven PDH and 51 from PLHIV with other fungal and bacterial infections as well as people without HIV. LFA devices were read manually (read by eye) and by an automated reader. Results: When the LFA was read manually, sensitivity was 96% and specificity was 90%. When an automated reader was used, sensitivity was 92% and specificity was 94%. The Kappa index comparing manual and automated reader was 0.90. Cross‐reactions were observed principally in samples from patients with proven diagnosis of paracoccidioidomycosis. Conclusions: The MiraVista ® Diagnostics Histoplasma antigen LFA had high analytical performance and good agreement between manual and automated reader. This LFA allows Histoplasma antigen testing with minimal laboratory equipment and infrastructure requirements.